Clonal evolution in long‐term follow‐up patients with hepatocellular carcinoma. Issue 11 (3rd October 2018) - Chen, Geng; Cai, Zhixiong; Li, Zhenli; Dong, Xiuqing; Xu, Haipo; Lin, Jianling; Chen, Lihong; Zhang, Huqin; Liu, Xiaolong; Liu, Jingfeng
Abstract : To investigate tumor clonal evolution in hepatocellular carcinoma (HCC), we collected 31 tumor samples, 16 peritumor samples and matched PBMCs from 11 long‐term follow‐up patients with HCC. Whole‐exome sequencing was performed to obtain SNVs and CNVs for each sample. An average of 652.2 somatic mutations were identified in each patient and the mean percentage of nonubiquitous tumor mutations was 63.7% (range, 0.7%–100%), reflecting the variety of tumor heterogeneity. Further analysis of clonal evolution was conducted based on mutation clustering results and revealed that different clonal evolution patterns indeed existed in single and multifocal HCC while these patterns were significantly correlated to patients' clinical course. These patterns clearly demonstrated different mechanisms of tumor recurrence. During tumor clonal evolution, potential therapeutic targets also emerged and vanished dynamically. Moreover, mutation analysis revealed that the contribution of mutational signature was correlated with clonal evolution history. Target sequencing of follow‐up plasma samples also confirmed that ctDNA level could dynamically reflect tumor clonal/subclonal burden. By investigating clonal evolution in HCC patients, our analysis revealed that different patterns indeed existed during HCC progression and proposed a novel strategy for identifying the origin of recurrent tumor as well as optimizing treatment selection. Abstract : What's new? Hepatocellular carcinoma is frequently deadly, in part because heterogeneity within the tumor allows the cancer to resist treatment. Here, the authors investigated how that heterogeneity develops by sequencing tumor samples to track clonal evolution. They performed whole‐exome sequencing to uncover how mutations arose and clustered within the tumor. The tumor's clonal evolution pattern, they found, correlated with the patient's clinical course. They observed therapeutic targets emerging and disappearing as the tumor evolved. The changing pattern of mutations in the tumor could be tracked by ctDNA. These findings could lead to improvements in prognosis and therapy for hepatocellular carcinoma.